Development of Adaptive Thermal Comfort Models for Residential Buildings in Sarawak Urban Areas - Tin, John Yuan En (Universiti Malaysia Sarawak (UNIMAS), 2018)
Energy consumption of building sectors has increased rapidly due to the improved living standard and the rise of resident’s expectations on thermal comfort. Mechanical ventilations especially air conditioning system is essential for hot and humid countries to achieve their ideal indoor comfort condition. However, such cooling system consumes a huge amount of electricity which is in contradiction with the concept of energy conservation. Thermal comfort assessment is one of the methods to overcome this issue. It evaluates the thermal perception of the occupants and consecutively facilitates the efficient usage of mechanical ventilation systems and attains the purpose of saving the energy. Steady state model and adaptive model are the two main approaches to evaluate thermal comfort. Fanger’s Predicted Mean Vote (PMV) model is a prevalent example of steady state model where environmental and personal factors are comprised. On the other hand, adaptive model involves comfort temperature and outdoor temperature to predict the thermal comfort of the indoor environment. Several research studies have indicated that PMV model is not applicable on tropical buildings as it often overestimates the actual thermal sensation of the occupants. Conversely, adaptive model is found to be expressing occupants’ thermal perception competently. In this study, thermal comfort analysis was carried out on the free running residential buildings in Sarawak which were naturally ventilated with minimal usage of mechanical ventilation systems. Physical measurements and subjective assessments were performed to evaluate the thermal responses of 287 residents based on ASHRAE scale, Bedford scale, thermal acceptability scale and thermal preference scale. PMV model was also used to predict the thermal sensation of the residents. Bedford scale showed the highest percentage of acceptable votes followed by ASHRAE scale, thermal acceptability scale and thermal preference scale. The comfort temperatures of the study were obtained from ASHRAE scale, Bedford scale and PMV model which were found to be 27.5 ℃, 28.1 ℃ and 26.2 ℃ respectively. The adaptive thermal comfort models were proposed based on the responses of residents on ASHRAE scale and Bedford scale. According to actual percentage dissatisfied which fulfilled 80% satisfaction, the upper and lower limit of the model for indoor operative temperature, relative humidity and air velocity were from 27.3 ℃ to 29.6 ℃, 74.0% to 92.0 % and 0.18 ms−1 to 0.66 ms−1 respectively.